Perceived stress and hair cortisol concentration in a study of Mexican and Icelandic women - Rebekka Lynch; Mario H. Flores-Torres; Gabriela Hinojosa; Thor Aspelund; Arna Hauksdóttir; Clemens Kirschbaum; Andres Catzin-Kuhlmann; Martín Lajous; Unnur Valdimarsdottir (Public Library of Science (PLoS), 2022)
Hair cortisol concentration (HCC) represent a potential biomarker of chronic psychological stress. Previous studies exploring the association between perceived stress and HCC have been limited to relatively small and selected populations. We collected hair samples from 881 women from the Mexican Teachers' Cohort (MTC) and 398 women from the Icelandic SAGA pilot-cohort following identical protocols. HCC was quantified using liquid chromatography coupled with tandem mass spectrometry. The self-reported Perceived Stress Scale (PSS, 10 and 4 item, range 0-40 and 0-16) was used to assess psychological stress. We conducted multivariable linear regression analyses to assess the association between perceived stress and log-transformed HCC in the combined sample and in each cohort separately. MTC participants had slightly higher HCC and PSS scores than SAGA participants (median HCC 6.0pg/mg vs. 4.7pg/mg and mean PSS-10 score 12.4 vs. 11.7, respectively). After adjusting for sociodemographic factors and health behaviors, we observed a 1.4% (95% CI 0.6, 2.1) increase in HCC for each unit increase in the PSS-10 score in the combined sample. Furthermore, PSS-10 quintiles were associated with a 24.3% (95% CI 8.4, 42.6, mean logHCC 1.8 vs 1.6) increase in HCC when comparing the highest to the lowest quintile, after multivariable adjustment. Similar results were obtained when we analyzed each cohort separately and when using the PSS-4. Despite relatively small absolute differences, an association between perceived stress and HCC was found in a sample of women from two diverse geographical and cultural backgrounds supporting the hypothesis that HCC is a viable biomarker in studies of chronic psychological stress.